Answer:
y = 5
Explanation:
Distribute the 7 to (y + 2) and distribute the -1 to (4y - 10).
7y + 14 - 4y + 10 = 44 - 2y + 5
Then add like terms, (7y - 4y), (10 + 14), and on the other side of the equation, (44 + 5)
3y + 24 = 49 - 2y
Add 2y to both sides, causing it to cancel out on one side, and on the other, solve 3y + 2y
5y + 24 = 49
Then subtract 24 from both sides, causing it to cancel out on one side, and on the other, solve 49 - 24
5y = 25
Then divide both sides by 5 and it cancels out on one side, and on the other solve 25/5
y = 5